REWARD AND PUNISHMENT IN ONLINE LEARNING PJOK OF THE COVID-19 PANDEMIC ON STUDENTS OF KARANGWINONGAN STATE SCHOOL, MOJOAGUNG - Eko Putut Dumiyanto; Galang Baqiyudin; M. Arfin Basri (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to determine the impact of rewards and punishments on physical education learning during the online Covid-19 pandemic for students at SDN Karangwinongan Mojoagung. The method used in this study is a survey method using a questionnaire or questionnaire. The study uses a questionnaire that has been filled out by 40 respondents . This data collection technique using a questionnaire is used to determine the impact of giving rewards and punishments in learning PJOK online during the Covid-19 Pandemic. Based on the description of the research data above, it shows that the impact of Reward and Punishment on physical education learning during the online Covid-19 pandemic is in the moderate category. The highest frequency is 29 students with a percentage of 39.3% in the medium category. The impact of Reward and Punishment in physical education learning during the Covid-19 pandemic, which was in the high category of 17.6% or 3 students, medium category 54.3% or 29 students, low category 28.3% or 8 students.